2021
DOI: 10.1021/acsnano.1c08432
|View full text |Cite
|
Sign up to set email alerts
|

Claudin-1-Targeted Nanoparticles for Delivery to Aging-Induced Alterations in the Blood–Brain Barrier

Abstract: Aging-induced alterations to the blood–brain barrier (BBB) are increasingly being seen as a primary event in chronic progressive neurological disorders that lead to cognitive decline. With the goal of increasing delivery into the brain in hopes of effectively treating these diseases, a large focus has been placed on developing BBB permeable materials. However, these strategies have suffered from a lack of specificity toward regions of disease progression. Here, we report on the development of a nanoparticle (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 83 publications
0
12
0
Order By: Relevance
“…The second approach involves cooperation with particular biomarkers overexpressed on various endothelial or epithelial cells. For instance, aging and injured BBB overexpressed claudin-1 more than health BBB; thus, peptide-modified claudin-1-targeted NPs could be mostly retained in injured brain microvascular endothelial cells and significantly boosted the drug delivery efficiency to the object region . The tumor-associated vascular and lymphatic endothelium significantly expressed membrane antigens, including endoglin, follicle-stimulating hormone receptor, and VEGFR2 .…”
Section: Applications Of Nanoparticles In Controllable Paracellular O...mentioning
confidence: 99%
See 2 more Smart Citations
“…The second approach involves cooperation with particular biomarkers overexpressed on various endothelial or epithelial cells. For instance, aging and injured BBB overexpressed claudin-1 more than health BBB; thus, peptide-modified claudin-1-targeted NPs could be mostly retained in injured brain microvascular endothelial cells and significantly boosted the drug delivery efficiency to the object region . The tumor-associated vascular and lymphatic endothelium significantly expressed membrane antigens, including endoglin, follicle-stimulating hormone receptor, and VEGFR2 .…”
Section: Applications Of Nanoparticles In Controllable Paracellular O...mentioning
confidence: 99%
“…ZO targeted peptide AT-1002 and claudin-1-targeted peptide C1C2 have been used to modify NPs, which is more targeted than NPs alone and opens the paracellular route more efficiently. 91,180 (ii) Peptides that target specific cells can be utilized to modify NPs. A CSK peptide, for example, has an affinity for goblet cells, the second largest colony of intestinal epithelial cells.…”
Section: Biomolecular Coronamentioning
confidence: 99%
See 1 more Smart Citation
“…These new versatile NPs can simultaneously carry imaging agents (MRI or PET), therapeutic drugs, and targeting ligands to induce a controlled drug delivery that can be activated by internal (pH, temperature, redox) or external stimuli (light, temperature, magnetic field, ultrasound). Bony et al reported a new NP to monitor alterations in the TJ protein expression (claudin-1) that may cause BBB leakiness through non-invasive MR imaging as well as a targeted delivery vehicle to improve site-specific target engagement of delivered therapeutics in old mice [ 218 ]. As examples of internal and external stimuli, Yang et al showed a dual-targeted therapeutic strategy in vitro and in vivo reported to enable pH-sensitive drug release and that allows cerebral ischemia targeting to improve stroke therapeutic efficacy [ 219 ].…”
Section: Bbb As a Target For Brain Aging And Cerebrovascular Disease ...mentioning
confidence: 99%
“…However, no efforts have been made on stroke prevention. The use of nanotechnology could facilitate access to the BBB [ 218 , 222 , 223 ] and open new and effective therapeutic targets to prevent the progression of chronic cerebral ischemia, the appearance of ischemic and haemorrhagic strokes, and cognitive deterioration associated with brain aging. To this end, further in vitro and in vivo studies should be developed in order to improve their applicability in clinical studies.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%